Effects of Numerical Mapping Techniques on Performance in Genomic Signal Processing - Gulocak, Seda Nur; Das, Bihter (CRC Press, 2023)
For genomic signal processing applications, analog DNA sequences need to be digitized. These numerical mapping techniques greatly affect the performance of the system in achieving the intended goal in genomic studies. The aim of this chapter is to analyze how the numerical mapping techniques used in the digitization of DNA sequences in the field of bioinformatics and which have gained popularity in recent years affect the performance in genomic studies. For this purpose, in the studies of the last 10â€‰years, all digital coding techniques presented in the literature were examined. In addition, numerical representations of these techniques were given in a sample DNA sequence, and the advantages and disadvantages of each coding technique were extracted. This study contains very useful information for future genomic signal processing applications. © 2024 selection and editorial matter, S. N. Kumar, Sherin Zafar, Eduard Babulak, M. Afshar Alam, and Farheen Siddiqui.